NanoBioTechnology : bioinspired devices and materials of the future - Shoseyov, Oded (Springer, 2017)
NanoBioTechnology: BioInspired Devices and Materials of the Future is a groundbreaking text that will assist scientists and students in learning the fundamentals and cutting-edge nature of this new and emerging science. Focusing on materials and building blocks for nanotechnology, leading scientists from around the world share their knowledge and expertise in this authoritative volume. The volume is broken into five sections. The first section presents an overview of nanotechnology and describes the many aspects of the field. Section 2 details biological materials serving as nanotemplates for bottom-up fabrication. Section 3 covers the use of biological macromolecules for electron transfer and computation. Section 4 presents a brief overview of the extensive and rapidly growing field of nanomedicine. Finally, Section 5 details de-novo designed structures and the various approaches different scientific groups take with molecular level training and language. Authoritative and comprehensive, NanoBioTechnology: BioInspired Devices and Materials of the Future provides an extraordinary and thorough overview of the emerging field of nanobiotechnology for engineers and physicists, chemists and biologists, and others from many diverse fields.